2013
DOI: 10.1128/jcm.00524-13
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the βLACTA Test, a Novel Commercial Chromogenic Test for Rapid Detection of Ceftazidime-Nonsusceptible Pseudomonas aeruginosa Isolates

Abstract: A novel commercial chromogenic technique, the ␤LACTA test (Bio-Rad, Marnes-la-Coquette, France), was evaluated to detect nonsusceptibility to ceftazidime in Pseudomonas aeruginosa isolates. Easily implemented in the routine microbiology laboratory, this rapid test was sensitive (95%) and specific (87%) and presented negative and positive predictive values of 99% and 100%, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 15 publications
2
6
0
Order By: Relevance
“…Our results are consistent with published data with respect to the low sensitivity of BLT in the detection of plasmid-encoded (CMY, DHA) or overproduced AmpC -lactamases(10,11). In contrast, K. oxytoca isolates with high-level expression of their chromosome-encoded β-lactamase were previously reported as being BLT-positive(10).…”
supporting
confidence: 94%
See 1 more Smart Citation
“…Our results are consistent with published data with respect to the low sensitivity of BLT in the detection of plasmid-encoded (CMY, DHA) or overproduced AmpC -lactamases(10,11). In contrast, K. oxytoca isolates with high-level expression of their chromosome-encoded β-lactamase were previously reported as being BLT-positive(10).…”
supporting
confidence: 94%
“…BLT can be applied directly to urine sediments (11). Recently, the test has been shown to detect ceftazidimenon-susceptible isolates of Pseudomonas aeruginosa with predictive negative and positive values of respectively 99% and 100% (12).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…However antimicrobial susceptibility testing is also essential for selecting the optimal treatment. Rapid resistance testing methods have been introduced in clinical microbiology laboratories for the detection of third generation cephalosporin-resistant Enterobacteriaceae (EB) and Pseudomonas aeruginosa or for the detection of methicillin resistance in Staphylococcus aureus [ 10 , 11 , 12 , 13 ]. These partial susceptibility tests have been validated for their diagnostic performance although their clinical impact has not been thoroughly assessed.…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary results suggested that this test is reliable for the detection of 3GC-resistant (3GC-R) Enterobacteriaceae (14). The test was recently evaluated in Pseudomonas aeruginosa to detect resistance to ceftazidime and was found sensitive (95%) and specific (87%) for this purpose (15). Here we report the result of a prospective multicenter study aiming at evaluating the performances of the BLT to rapidly detect resistance to 3GC in clinical isolates of Enterobacteriaceae.…”
mentioning
confidence: 99%